Influence of the capital structure in the investments in innovation of the industries listed on the BM&FBOVESPA [doi: 10.21529/RECADM.2017002] - Rafael Sales Almendra; Alessandra Carvalho de Vasconcelos; Rayane Nogueira Aragão; Ione Azevedo Cysne (Revista Eletrônica de Ciência Administrativa, 2017)
In this study the influence of the capital structure in the investments in innovation of 120 industries listed on the BM&FBovespa was analyzed in the period from 2013 to 2015. As proxies for capital structure, we consider short-term, long-term and total debt. In order to represent the investments in innovation, the number of registered patents and the percentage of expenditure in with R&D in relation to sales were considered. Through the Fischer LSD Test, it was possible to verify that companies that do not invest in innovation have higher debts. Through linear regression with panel data, it was verified that only the long-term and total debts have a positive influence on innovation investments through patents. Therefore, the results suggest that own resources may be insufficient to investments in innovation, leading third parties resources to contribute to the increase of investments in innovation through patent registration as stated by the Pecking Order Theory, as well as to collaborate to the reduction of agency costs, limiting the role of the managers, as proposed by the Agency Theory.   Keywords Capital structure; Investments in innovation; Pecking Order Theory; Agency Theory.